Material Passports in Construction Waste Management: A Systematic Review of Contexts, Stakeholders, Requirements, and Challenges - Lawrence Martin Mankata; Prince Antwi-Afari; Samuel Frimpong; S. Thomas Ng (Buildings)
The growth in the adoption of circular economy principles in the construction industry has given rise to material passports as a critical implementation tool. Given the existing problems of high resource use and high waste generation in the construction industry, there is a pressing need to adopt novel strategies and tools to mitigate the adverse impacts of the built environment. However, research on the application of material passports in the context of construction waste management remains limited. The aim of this paper is to identify the contextual uses, stakeholders, requirements, and challenges in the application of material passports for managing waste generated from building construction and demolition processes through a systematic review approach. Comprehensive searches in Scopus and the Web of Science databases are used to identify relevant papers and reduce the risk of selection bias. Thirty-five (35) papers are identified and included in the review. The identified key contexts of use included buildings and cities as material banks, waste management and trading, and integrated digital technologies. Asset owners, waste management operators, construction and deconstruction teams, technology providers, and regulatory and sustainability teams are identified as key stakeholders. Data requirements related to material, components, building stock data, lifecycle, environmental impact data, and deconstruction and handling data are critical. Moreover, the key infrastructure requirements include modeling and analytical tools, collaborative information exchange systems, sensory tracking tools, and digital and physical storage hubs. However, challenges with data management, costs, process standardization, technology, stakeholder collaboration, market demand, and supply chain logistics still limit the implementation. Therefore, it is recommended that future research be directed towards certification and standardization protocols, automation, artificial intelligence tools, economic viability, market trading, and innovative end-use products.